Tác động của trách nhiệm xã hội đến hiệu quả hoạt động của các doanh nghiệp vừa và nhỏ. Vai trò trung gian của giữ chân khách hàng và đổi mới xanh - Lê Thanh, Tiệp (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
This study assesses the impact of corporate social responsibility (CSR) on corporate performance and then examines the mediating role of customer retention and green innovation. To achieve these objectives, a survey included 479 middle and senior managers at SMEs in the food manufacturing and processing industry in Vietnam. The study employs qualitative combined with quantitative methods to analyze, the results show that CSR plays an important role in enhancing customer retention and green innovation of enterprises, leading to enterprises’ operational efficiency. The novelty of this study is to provide insight into how CSR enhances corporate performance by examining a rational analytic model under which customer retention and innovation play a mediating role in this relationship. The results of this study are useful to entrepreneurs and corporate managers in their efforts to promote the performance of SMEs in Vietnam in a sustainable way.